Political Motives of Islamic Parties in Nominating Celebrities as Legislative Candidates for the 2024 Elections - Dimas Subekti; Ridho Al-Hamdi (Jurnal Pemerintahan dan Kebijakan (JPK), 2023)
The National Mandate Party (PAN) is the largest Islamic party that supports legislative candidates from among artists. Therefore, this study aims to explain PAN’s political motives in supporting legislative candidates from among artists for the 2024 elections. This research used a qualitative method with a case study approach. The findings explained that the political motives of material incentives and solidarity dominated PAN’s political recruitment. The material incentive motive is that artist candidates are used as a voter-getter strategy based on their financial strength and popularity. Then, the solidarity incentive political motive tends to be related to emotional and moral relationships. On the emotional side, PAN believes in supporting artist candidates again because it reflects their significant contribution to the party’s internal and parliamentary elections. Meanwhile, from the moral side, PAN has a specific goal to convey to the public that the party has an inclusive principle for all groups. It contradicts the Islamic religious identity attached to PAN, which is not specifically shown in nominating legislative candidates for the 2024 elections.